Content of Medicinal Chemicals in Traditional Herbal Medicine: A Systematic Literature Review - Lia Fikayuniar; Mentari; Ainun Mar’atus Putri Warsito; Refriyanti Irma; Elista Indah Susanti (HM Publisher, 2024)
Jamu is a traditional medicine made from natural ingredients that are known to be inherited from generation to generation for health. The more widespread the use of traditional medicines is, the more opportunities there are for the adulteration of the ingredients. There are even some herbal medicines that contain medicinal chemicals (BKO). Traditional medicines are prohibited from containing BKO because the BKO content in herbal medicine can be a source of danger in herbal medicine. The method used in this research is data collection carried out by searching databases taken from various scientific articles sourced from PubMed, Science Direct, ResearchGate, WoS (Web of Science), and Google Scholar with articles that have been published from 2013 - 2023. The results that have been obtained from several studies that have been carried out show that there is BKO content in traditional herbal medicine that has been circulating in the community, such as paracetamol, mefenamic acid, phenylbutazone, allopurinol, piroxicam, prednisone, and others.